MET exon 14 skipping mutation in triple-negative pulmonary adenocarcinomas and pleomorphic carcinomas: An analysis of intratumoral MET status heterogeneity and clinicopathological characteristics. (April 2017) - Kwon, Dohee; Koh, Jaemoon; Kim, Sehui; Go, Heounjeong; Kim, Young A; Keam, Bhumsuk; Kim, Tae Min; Kim, Dong-Wan; Jeon, Yoon Kyung; Chung, Doo Hyun
Highlights: MET mutations is detected in 8.8% of triple-negative adenocarcinomas of the lung. MET mutations is detected in 20% of pleomorphic carcinomas of the lung. MET -mutated adenocarcinoma is characterized by older age and an acinar histology. MET gene amplification might occur in the tumor cells harboring the MET mutation. Abstract: Objectives: MET mutations leading to exon 14 skipping rarely occur in non-small cell lung cancer (NSCLC). Recently, small molecule inhibitors targeting MET mutations showed clinical benefit. However, the clinicopathological characteristics of NSCLC harboring MET mutations, and the correlation among mutations, protein expression, and gene copy number of MET in NSCLC remain unclear. Therefore, we address these issues. Materials and methods: MET exon 14 skipping mutations were evaluated using real-time quantitative reverse-transcription-PCR (qRT-PCR) in 102 triple-negative (i.e., EGFR mutation (−)/ ALK translocation (−)/ KRAS mutation (−)) pulmonary adenocarcinomas, and 45 pleomorphic carcinomas. MET mutation and gene copy were also examined in microdissected tissues obtained from tumor areas with heterogeneous MET immunohistochemical expression. Results: MET mutations were detected in 8.8% (9/102) of triple-negative adenocarcinomas and 20% (9/45) of pleomorphic carcinomas of the lung. Patients with MET -mutated adenocarcinomas was significantly older than those without MET mutations ( P  = 0.015). The male to female and ever-to never-smoker ratios were 3:6 and 2:7, respectively, among patients with MET -mutated adenocarcinomas. All (9/9) of the MET -mutated adenocarcinomas showed acinar predominant histology with associated lepidic patterns. In contrast, the male to female and ever- to never-smoker ratios were 8:1 and 7:1, respectively, among patients with MET -mutated pleomorphic carcinomas. The carcinoma component of MET -mutated pleomorphic carcinomas was mostly adenocarcinoma of acinar pattern (8/9). MET mutation was detected by qRT-PCR in all samples with heterogeneous MET expression microdissected from five cases with MET -mutated adenocarcinoma, while MET gene amplification was detected in tumor areas expressing high MET protein levels among MET -mutated adenocarcinomas. Conclusion: MET -mutated NSCLC is characterized by older age in patients with adenocarcinoma and by an acinar histology and variable MET expression in patients with adenocarcinoma and pleomorphic carcinomas. Moreover, MET gene amplification might occur in the tumor cells harboring the MET mutation.